IMPLEMENTATION OF NON CONVICTION BASED ASSETS AGAINST MONEY LAUNDERING AND MONEY CHANGING CRIMES IN INDONESIA - Insan Pribadi (JIL : Journal of Indonesian Law, 2021)
Money Laundry is an extraordinary crime with the act of hiding or disguising the money or assets obtained from the proceeds of a crime. Money Laundry is closely related to other criminals, including corruption as a predicate crime. Due to the development of criminal acts, a new breakthrough emerge which was echoed in The United Nations Convention Against Corruption in 2003 named Non-Conviction Based Asset Forfeiture, which is a legal mechanism that allows the owned assets that have been taken by criminals and is possible to be confiscated again.